Japan's dependence on the world economy : - Hollerman, Leon (Princeton University Press, 1967)
Professor Hellerman analyzes the interrelations between changes in the structure of Japan's industrial production and the structure of its foreign trade. Applying the theory of industrial organization at the international level, he proceeds from the examination of structure to an evaluation of performance and public policy in Japan's external economic affairs